Les moulins de l’Antiquité tardive en Gaule méridionale : l’exemple des meulières de Saint-Quentin-la-Poterie (Gard) - Samuel Longepierre (Gallia)
How can milling activities in Late Antique Gallia Narbonensis be defined? How important were they within the family setting? Did water mills and bakeries, well represented since the Early Empire, grow or decline in number? How was trade in millstones organized along with their production centres? These issues will be addressed through the study of one particular centre, that of Saint-Quentin-la-Poterie (Gard). Active since the Early Empire, it was particularly dynamic in the 5th and 6th c. AD. It consists of one extraction site divided into concessions and four rural establishments housing workshops for the shaping of the millstones. One of them, the Roquésis villa, has been the subject of a research excavation. The types of millstones produced in Saint-Quentin-la-Poterie are also compared with those found more broadly on Late Antique occupation sites in southern Gaul. The products of various quarries, they provide information on the main categories of mills during this period and on their evolution.